Strategi Sekolah Menengah Pertama dalam mengimplementasikan Kurikulum Merdeka - Ramadhan, Iwan (Academy of Education Journal, 2024)
This research aims to determine the implementation of the independent curriculum at SMP Negeri 9 Pontianak which is a driving school and the independent curriculum system implemented in grade 7. The learning system approach reflects an educational philosophy that provides space for creativity, independent thinking and greater understanding of students. The P5 chosen were local culture, entrepreneurship and sustainable living. This research method uses descriptive qualitative. The research population is teachers and students of SMP Negeri 9 Pontianak, the research sample consists of teachers, curriculum assistants and students. Research analysis was carried out according to Milles and Huberman's analysis. The research results show that at the beginning of the learning process there must be cognitive diagnostic tests and non-cognitive tests. At the end of the teaching and learning process. This diagnostic planning assessment is made by the teacher. Difficulties in implementing the independent curriculum at SMP Negeri 9 Pontianak were overcome by providing special trainers by the education center, conducting IHT house learning, every Friday the school has a meeting to discuss obstacles related to implementing the independent curriculum and the four SMP Negeri 9 have their own application provided by the government called Merdeka Learning contains information about the independent curriculum, such as providing training topics for teachers, references for teaching tools and teachers can also find out students' ability levels.